PRIVATE FUNDS FINANCING OF EUROPEAN HIGHER EDUCATION - MARIA MĂCRIŞ; ADRIAN MĂCRIŞ (Annals of the University of Petrosani: Economics)
Higher education plays an important part in the European society, creating knowledge applicable to society and economy, and generating the process of economic and social evolution. Higher education institutions in Europe try to modernize both at the level of the courses they offer and at the level of their acting manner; European states as well as the private agents involved try to find out new, improved means of coordinating and financing. Starting from this idea, we would like to carry out an analysis of the manner of financing European higher education out of private funds with a view to identify new financing sources.